ANALISIS KEPUASAN PENGGUNA DAN TATA KELOLA LAYANAN INTERNET KAMPUS BERBASIS KERANGKA KERJA ITIL: STUDI KASUS UNIVERSITAS BANGKA BELITUNG - Umar Faruq Vista; Davin Pramudia; Okki Darmawan; Iski Zaliman; Taqwa Martadinata (LPPM UNIVERSITAS BINA INSAN, 2026)
For conducting academic activities at the University of Bangka Belitung (UBB), it has become necessary to have access to services of internet network (WiFi). Ineffective responses to network failure and poor network connectivity indicate that there has not been appropriate technical service management despite such high dependence on WiFi services at UBB. The objective of this study is to evaluate the WiFi network quality at UBB and propose a strategy for improving IT governance. The problem will be addressed by utilizing the combination of ITIL 4 methodology as a basis for development of SOPs and ServQual approach for assessment of the gap between customers' expectations and perceptions. Poor results were found in all five service quality dimensions as assessed empirically based on 376 student respondents. Responsiveness (-2.30) and Reliability (-1.85) were found to be the dimensions where there was the greatest difference. The improvement recommendations proposed by this study in relation to ITIL 4 framework are linked to three important practices: Incident Management, Service Desk, and Service Level Management, which aim at rectifying the managerial deficiencies identified in the study. There is an expectation that the information technology support services will shift towards a proactive approach aimed at creating shared value.